Physicochemical and Stability of Goat Cheese with Mono and Mixed Culture of Lactobacillus plantarum and Lactobacillus rhamnosus - Setiawardani, Triana; Rahayu, Winiati Pudji; Palupi, Nurheni Sri (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
The purpose of the study is to assess the effect of the use of mono probiotic culture and mixed cultures of Lactobacillus plantarum and Lactobacillus rhamnosus on the physicochemical properties and its viability during storage. The soft cheeses were made through three treatments: (1) the use of Lactobacilllus rhamnosus culture, (2) the use of Lactobacillus plantarum culture and (3) the use of mixed cultures (Lactobacillus rhamnosus and Lactobacillus plantarum). The variables measured were the cheese texture (firmness and stickiness), proximate, pH of the product, and the number of LAB. The results showed that cheese firmness ranged from 10.78 to 47.75 gf, cheese stickiness was -8.23 to -11.53 gs, cheese pH was 4.70 - 5.60; number of cheese LAB was 8:59 - 9.69 log cfu/g. The content of protein, fat, and ash were 13.65-16.54%, 15:28-20:03%, and 2.7-3.39%, respectively. The conclusion of this study was that the soft cheeses with mixed cultures of L.rhamnosus and L.plantarum are potentially good to be developed as a probiotic food.